2013
DOI: 10.1002/jgrd.50290
|View full text |Cite
|
Sign up to set email alerts
|

Influences of the Atlantic Ocean on the summer precipitation of the southeastern Tibetan Plateau

Abstract: The southeastern Tibetan Plateau is one of the predominant summer rainfall regions in the world and is also the crucial water vapor channel of the Asian summer monsoon. The rainfall variability in the region influences not only the local communities but also downstream communities in East Asia. However, previous studies have exhibited large rainfall biases in this region in state‐of‐the‐art climate models. Understanding the observed rainfall variability provides an opportunity to identify the origin of model b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 53 publications
(68 reference statements)
1
25
0
Order By: Relevance
“…Furthermore, the regression patterns of the 200 hPa Eliassen-Palm (EP) stationary wave flux with the NAO index exhibit an unusual EP stationary wave flux along the aforementioned wave train, illustrating the downstream energy flux from the North Atlantic to the TP (Figure 3). Thus, based on these detailed analyses of geopotential heights, stationary wave flux and previous research (Bothe et al, 2010Zhu et al, 2011;Gao et al, 2013), the aforementioned wave train related to the NAO acts as a bridge to connect the North Atlantic to the TP.…”
Section: The Anomalous Atmospheric Circulation Associated With the Naomentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the regression patterns of the 200 hPa Eliassen-Palm (EP) stationary wave flux with the NAO index exhibit an unusual EP stationary wave flux along the aforementioned wave train, illustrating the downstream energy flux from the North Atlantic to the TP (Figure 3). Thus, based on these detailed analyses of geopotential heights, stationary wave flux and previous research (Bothe et al, 2010Zhu et al, 2011;Gao et al, 2013), the aforementioned wave train related to the NAO acts as a bridge to connect the North Atlantic to the TP.…”
Section: The Anomalous Atmospheric Circulation Associated With the Naomentioning
confidence: 99%
“…Yang et al (2004) documented that the strength and shift of the Middle East jet stream, the associated stationary wave activity flux and high-frequency eddy activities may be affected by the winter and spring North Atlantic Oscillation (NAO), which subsequently affect the downstream Asian summer monsoon system that dominates the TP. Gao et al (2013) revealed that Atlantic sea surface temperature anomalies have the greatest control over the southeastern TP summer precipitation via a Rossby wave response. Using mass balance measurements of the Zhadang Glacier and combined atmospheric-glacier modelling, Mölg et al (2014) reported that the mid-latitude climate should be considered as a possible driver of past and future glacier changes over the southern TP; this finding agrees with the underestimated effects of mid-latitude westerlies on precipitation over the TP .…”
Section: Introductionmentioning
confidence: 99%
“…The precipitation over the TP, which is situated in the Asian monsoon region, is influenced greatly by changes in large-scale monsoon circulation. Many studies have also emphasized the importance of Eurasian snow cover [Xu and Lu, 1992], sea surface temperature (SST) in the Atlantic Ocean and the Indian Oceans [Gao et al, 2013;Hu and Duan, 2015], and atmospheric internal variability [e.g., Liu and Yin, 2001;Zhu et al, 2011; for regulating the spatial and temporal patterns of TP summer precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…It forms as a result of the propagation of quasi-stationary Rossby waves along the Asian jet and has a wavelength of about 60 ∘ in the zonal direction (Lu et al, 2002;Enomoto et al, 2003;Sato and Takahashi, 2003;Kosaka et al, 2009Kosaka et al, , 2012. SRP is viewed as a part of the circumglobal teleconnection (CGT) pattern that extends zonally through the whole hemisphere (Ding and Wang, 2005;Yasui and Watanabe, 2010;Chen and Huang, 2012;Lin, 2014) and can influence climate over a broad area, including precipitation and temperature over TP and East Asia (Liu and Yin, 2001;Wu, 2002;Bothe et al, 2010Bothe et al, , 2011Gao et al, 2013). Gao et al (2013) studied the variation of summer precipitation over the southeastern part of TP, and emphasized the importance of Atlantic SST anomalies by triggering CGT-like zonal wave pattern.…”
Section: Introductionmentioning
confidence: 99%
“…SRP is viewed as a part of the circumglobal teleconnection (CGT) pattern that extends zonally through the whole hemisphere (Ding and Wang, 2005;Yasui and Watanabe, 2010;Chen and Huang, 2012;Lin, 2014) and can influence climate over a broad area, including precipitation and temperature over TP and East Asia (Liu and Yin, 2001;Wu, 2002;Bothe et al, 2010Bothe et al, , 2011Gao et al, 2013). Gao et al (2013) studied the variation of summer precipitation over the southeastern part of TP, and emphasized the importance of Atlantic SST anomalies by triggering CGT-like zonal wave pattern. At present, the researches about the HMs are rare, and most of them focus on the analysis of main meteorological elements.…”
Section: Introductionmentioning
confidence: 99%